Customer Engagement Marketing and Firms’ Deliberation on E-Word of Mouth Communication on Online Platforms : A Study on Millennials and Zoomers - Nandi, Shampa; Prasad, S. Shyam (Indian Journal of Marketing, 2024)
Purpose : Customer engagement (CE) has become extremely popular since social media emerged. However, there is disagreement over the proper definition, metrics, and operationalization of CE in social media and its implications. It is unclear how millennials and zoomers use social media and what tactics firms can use to improve CE. This study aimed to investigate and quantify CE for millennials and zoomers in social media. Methodology : We quantified CE through its three dimensions, namely Vigour, Absorptions, and Dedication and measured its impact on electronic word-of-mouth (eWOM) communication. Using structural equation modeling based on 250 responses obtained using a purposive sample strategy, we evaluated the difference in CE across two generation cohorts. We also looked at the effect of the enterprises’ purposeful approach. Findings : There was no discernible difference in the relationship between zoomers and millennials regarding CE and eWOM. The intentional strategy of the companies had little effect as a mediating factor between eWOM and CE. Practical Implications : Our research provided profound insights into the use of social media by techsavvy generations through an exploration of the three dimensions of CE. It discussed how a customer adds value to any company through eWOM. This would allow the managers to involve customers in brand promotion through social media, segment the market, and develop more successful marketing plans. Originality : The study model examined the effects of eWOM communication, which is the first type, by combining the original CE components with the age cohort as a moderator and the firm’s strategy as a mediating variable.